POLYHARMONIC DETECTOR OF WEAK SPHIGMOMETRIC SIGNALS - PYVOVAR, OLEG; PIDCHENKO, SERHII; TARANCHUK, ALLA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The application of chaotic modes of nonlinear dynamics is valid within the process of description and study of circulatory processes in the human body. Such an approach can potentially ensure the most plausible reproduction and reliability of the detection of weak biological images of signals in conditions of powerful interference arising from other systems of the human body and through external influences.The essence of the method of detecting polyharmonic signals by a chaotic detector is to use sharp transitions between chaotic and periodic modes of operation during the action of the detected signal. The weak signal processing circuit is actually a nonlinear filter with a certain frequency resource. The simulation of the nonlinear Duffing system allowed us to conclude that the frequency resource of such a chaotic detector is sufficient to detect not only weak harmonic but also polyharmonic signals against the background of powerful fluctuation noise. In this case, the operating frequency range of the chaotic detector is up to a decade, and the reaction of the nonlinear system in the phase plane with respect to the action of the harmonic signal generally does not change.A simulation model (Simulink) and a reconstruction of sphygmometric sensor signals for modeling in conditions of powerful interference were developed. The possibility of detecting a polyharmonic signal with a high level of reliability under the condition of signal-to-noise ratio up to -20 dB, and with a permissible level of reliability – up to -37 dB in real time, is shown. The possibility of detecting polyharmonic signals by a chaotic detector in the conditions of fluctuating non-Gaussian noise according to different criteria of discrimination of chaotic generator operating modes is also confirmed.The confirmed properties of the chaotic detector allow the analysis and diagnosis of the human condition according to the main first harmonics of the spectrum of the weak sphygmometric signal, which determine the nature of the disease of the cardiovascular system. The proposed method of detecting sphygmometric signals by the chaotic detector can be used for non-contact study of pulse wave signals by remote non-contact sensors, the work of which is associated with the appearance of a high level of interference ..
Keywords: nonlinear system; chaotic generator; polyharmonic signal; chaotic detector